Learning Model Problem Solving Problem Solving to ImproveSkills in Electrolyte and Non-Electrolyte - Ila Rosilawati; Yesi Aniende; Nina Kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Abstract:Problem Solving Model to Improve Problem Solving Skills in Electrolyte and Non Electrolyte Solution. This study aims to describe the effectiveness of problem solving learning models in electrolyte and non-electrolyte solution materials to improve problem solving skills. The research method used was a quasi-experimental method with the matching only pretest-posttest control group design. The population of this study were all students of class X IPA SMA AL-Azhar 3 Bandarlampung in the 2019/2020 academic year. The research sample was determined by purposive sampling technique, so that the students of class X IPA 4 as the experimental class and class X IPA 3 students as the control class were determined. The data analysis technique used is the difference test of the two means. The results showed the n-gain of problem solving skills in the experimental class was 0.57 which was categorized as moderate; There is a significant difference in the average post-test score between the experimental class and the control class. Based on these results, it can be concluded that the problem solving learning model in electrolyte and non-electrolyte solution material is effective for improving problem solving skills.Keywords: Model, Problem Solving Problem Solving Skills, Electrolyte and Solutions Non-Electrolyte